The Silver Witch - Brackston, Paula; Mitchell, Ellisa (New York : Thomas Dunne Books/St. Martin's Press, 2015)
"A year after her husband's sudden death, ceramic artist Tilda Fordwells finally moves into the secluded Welsh cottage that was to be their new home. She hopes that the tranquil surroundings will help ease her grief, and lessen her disturbing visions of Mat's death. Instead, the lake in the valley below her cottage seems to spark something dormant in her a sensitivity, and a power of some sort. Animals are drawn to her, electricity shorts out when she's near, and strangest of all, she sees a new vision; a boatful of ancient people approaching her across the water. On this same lake in Celtic times lived Seren, a witch and shaman. She was respected but feared, kept separate from the community for her strange looks. When a vision came to her of the Prince amid a nest of vipers she warned of betrayal from one of his own. Prince Brynach both loved and revered her, but could not believe someone close to him wished him harm, even as the danger grew. In her own time, Tilda's grief begins to fade beside her newfound powers and a fresh love. When she explores the lake's ancient magic and her own she discovers Seren, the woman in her vision of the boat. Their two lives strangely mirror each other's, suggesting a strong connection between the women. As Tilda comes under threat from a dark power, one reminiscent of Seren's prophecy, she must rely on Seren and ancient magic if death and disaster is not to shatter her life once more. "--
"Thomas Dunne Books."
Keywords: Witches -- Fiction; FICTION / Historical; FICTION / Fantasy / Historical; Occult fiction